Utility of Water Conservation in India: Critical Water Conservation Initiatives for Sustainable Future (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Water has long been regarded as the liquid of life. Organisms of all sorts of animals are necessary to work properly. It is possible to live without food for many weeks, but not even for many days without water. Plants and animals, we feed still need nutrition, meaning that the water shortage eventually transforms into a life crisis. It is also clear that water is essential to support life. Although 71 of the earth's surface is filled by water systems, more than 20 of humans face a significant water shortage. 97.3 percent of the water on the surface of the planet is saline. Just 2.7 of surface water is available as drinkable for humans. With the increasingly increasing population, with a limited amount of the world's water, this valuable resource needs to be protected and preserved. Recycling and water conservation is more significant in India as India holds just 2.42 of water supplies, which is just 145th of the world's total although it contains nearly 17 of the world's people, which is essentially 16th of the world's population. There are just 4 percent of the world's fresh water supplies, only 125 of the Earth's total drinking water. Conservation of water requires the prudent usage and sufficient care of a finite quantity of water. Given that we all depend on water to support existence, it is our duty to learn more about water management and how we can help maintain our resources clean and stable for future generations. Conservation of water takes considerable work, benefits every bit. It is therefore false that the position of a person does not matter. This thesis explores the significance of water management and critical water conservation initiatives in the present time.